2005
DOI: 10.2134/agronj2004.0249
|View full text |Cite
|
Sign up to set email alerts
|

Extractable Soil Phosphorus and Inorganic Nitrogen following Application of Raw and Anaerobically Digested Swine Manure

Abstract: Processing of swine (Sus scrofa domestica) manure in an anaerobic Due to a potential increase in the use of anaerobic digester for biogas production is not a complete waste treatment process. Therefore, digested manure must be utilized in some manner, digestion systems for energy production, there is need most likely as a source of plant nutrients. The objective of this study for a reliable estimate of plant-available N and P in diwas to compare the effect of raw and digested liquid swine manure gested swine m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 23 publications
5
35
2
Order By: Relevance
“…Conversely, Loria and Sawyer [77] reported that raw and digested swine manure generated similar net inorganic N and mineralization, although the chemical oxygen demand (COD) was significantly decreased after digestion. Rubaek et al .…”
Section: Effects Of Biogas Residue On Plant Growthmentioning
confidence: 99%
“…Conversely, Loria and Sawyer [77] reported that raw and digested swine manure generated similar net inorganic N and mineralization, although the chemical oxygen demand (COD) was significantly decreased after digestion. Rubaek et al .…”
Section: Effects Of Biogas Residue On Plant Growthmentioning
confidence: 99%
“…No credits for mineral fertiliser replacement are given to the digestate because the fertilizing properties of digestate and raw manure are considered equivalent in the long term [39][40][41]. Fertiliser credits are not given to energy crops systems as the digestate produced is recycled in the same fields where the crops are grown, and the reduced need for mineral fertiliser is already accounted for.…”
Section: Functional Unit and System Boundariesmentioning
confidence: 99%
“…Nitrification rates may vary from 0.98 to 1.53 kg ha -1 day -1 in manured soils, as observed by Aita et al (2006) in an assessment carried out four days after pig slurry applications of 40 and 80 m 3 ha -1 , respectively, and all ammoniacal N present in manure can be nitrified within 10 days after manure application (Chantigny et al, 2001). This rapid transformation of ammoniacal N to N-NO 3 -significantly increases the concentration of N-NO 3 -in soil (Loria & Sawyer, 2005). However, accumulation of N-NO 3 -in soil occurs in the first days after pig slurry application (Chantigny et al, 2004;Assmann et al, 2007;Adeli et al, 2008) and decreases over time due to its transfer by runoff (Smith et al, 2001a;Ceretta et al, 2010) and, mainly, percolation (Daudén et al, 2004;Basso et al, 2005;Bergström & Kirchmann, 2006), as it forms an outer-sphere complex with low binding energy with surface functional groups of reactive soil particles.…”
Section: Introductionmentioning
confidence: 99%